Review of Admirandus Belogurov & Belogurova, 1979 (Nematoda, Oncholaimidae) with the description of a new species and the first record of the genus from Brazil - Cavalcanti, Mariana Da Fonseca; Guilherme, Betânia C.; Rosa-Filho, José Souto (Zootaxa, 2023)
The present study provides a description of a new Admirandus species from northeastern Brazil, together with an updated species identification key. Admirandus capibaribei sp. n. can be distinguished from all the other Admirandus species by its physical dimensions (body length, a, stoma and spicule ratios), sexual dimorphism of the tail, the absence of pre-cloacal supplements, and the presence of a row of denticles at the base of the right ventrosublateral tooth. While Admirandus has been reported from temperate, subtropical and tropical environments around the world, this is the first record of the genus from Brazil. Further research on Admirandus and other Adoncholaiminae species, which include the integration of morphological and molecular approaches, will be important to provide a better understanding of the taxonomy of this group, as well as on its demanian system.